Sipakatau, Sipakainge, Sipakalebbi, Siri Na Pace: A Multicultural Counseling Model in Terminating Moral Degradation - Izramadhani, Nur Suci; Bakhtiar, Muhammad Ilham; Ahmad Yusuf; Syaifullah Nur; Sutra Awaliyah; Sabil Husin (ILIN Education Indonesia, 2024)
This study discusses the development of a multicultural counseling model based on 4S cultural values to terminate moral degradation among adolescents which is one of the factors that cause various social problems. This study generally aims to present a multicultural counseling service guide for guidance and counseling teachers. The specific objectives of this study are: 1) To describe students' needs for a multicultural counseling model based on 4S cultural values